The Fractionation of Transfer Ribonucleic Acid from Roots of Pea Seedlings - Vanderhoef, Larry N. (1970)
Isoaccepting transfer RNA species for several amino acids were fractionated by reverse phase column chromatography. Transfer RNA from dividing cells of pea (Pisum sativum) root was compared to that from nondividing cells, and no relative quantitative or qualitative differences were noted for the transfer RNA species for leucine, lysine, proline, threonine, methionine, serine, and phenylalanine. However, certain artifactual differences for serine and phenylalanine were noted. Quantitative differences were observed in tyrosyl-transfer RNA's. Ribonuclease action on tRNA did not contribute to the tRNA species observed.